MRI-Ultrasound Fusion Imaging for Diagnosis of Deep Infiltrating Endometriosis – A Critical Appraisal - Berger, Judith; Henneman, Onno; Rhemrev, Johann; Smeets, Maddy; Jansen, Frank Willem (Ultrasound International Open, 2018)
It was the aim of our study to evaluate this procedure using pelvic anatomical landmarks in order to assess the accuracy of fusion imaging and to critically evaluate the applicability in daily practice.In a prospective, single center study, 10 patients with clinical signs of deep infiltrating endometriosis (DIE) were selected. We measured the distance between the landmark organ and the target shown by the software system (measurement 1). Measurement 2 depicts the distance between the landmark and the nearest calibration point. The calibration inaccuracy was measured as a third type of measurement (measurement 3).Measurement 1: the average distance between the organ landmark to the target was 13.6 mm (range: 0–96 mm). Measurement 2: in 31 of the 40 attempts (77.5 %), we could measure the distance from the landmark organ to the nearest calibration point. The average distance was 34.4 mm (range: 0–69 mm).Measurement 3: A perfect match was seen in 6 of 20 attempts (30.0 %). There was a deviation in 14 of the 20 attempts (70.0 %). The mean distance was 11.1 mm (range: 6–23 mm). Conclusion Although very promising, MRI-ultrasound fusion imaging (MUFI) currently cannot be readily implemented into daily practice as a routine evaluation of DIE.